Maternal care with children’s health in home environment compared to health service - Joana de Ângelis Ponte e Silva; Deborah Gurgel Freire; Maria de Fátima Antero Sousa Machado (Rev Rene)
Maternal care consists of a set of actions that allow growth and healthy development for the child. The objective of this study was to identify maternal care provided to children in home environment and the difficulties they encounter in the health service. This is a descriptive study with qualitative analysis. The study was conducted in a Basic Health Unit of the Family in the city of Fortaleza, in 2009. 12 mothers were assessed through a semi-structured interview. Their speeches were analyzed and organized in frames regarding the subject. It was noticed that most mothers had used drugs before seeking health care. As preventive measures there was concern with food and home. Yet the difficulties were pointed out regarding the care, accessibility and available medicine. Yet, it was observed that mothers seek resoluteness towards the illness of her child, making use of resources that could potentially increase the health of the child.